(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
An experiment was conducted to assess the influence of edible coatings on postharvest quality of mandarin during 20 days of ambient storage. Sorted fruits were washed; fruit surface water was removed and then coated with 100% liquid paraffin wax, 0.5% chitosan, 1.0% chitosan, 1.5% chitosan, and 100% coconut oil. After coating, fruit surface was air dried and kept at ambient condition (25±3 °C, 60–70% RH) and analyzed periodically for weight loss, respiration rate, firmness, decay incidence, TSS, pH, ascorbic acid content, and sensory properties. The results revealed that coconut oil had immense effect on the reduction of the weight loss and respiration rate and preserved firmness, total soluble solids, ascorbic acid, total sugar and reducing sugar and no incidence of moulds & their growth was found up to 16 days of storage. Int. J. Agril. Res. Innov. & Tech. 8 (1): 18-25, June, 2018